Factors associated with stockout of Nevirapine syrup in Oshana Region, Namibia - Emmanuel Magesa; Kabwebwe Honore Mitonga; Penehafo Angula (AOSIS, 2020)
Infants who are born with HIV/AIDS is still a public health concern in developing countries, especially in Sub Saharan Africa. In Namibia, it is estimated that the prevalence rate of HIV pregnant women is around 17.2%, makes it to be among the countries with the highest prevalence rates among HIV women in sub-Saharan Africa (SSA). Some improvement regarding Prevention of Mother to Child Transmission has been made, however, frequent stock out of Nevirapine syrup continues to slow down, government efforts to foster the emergence of an HIV-free generation of Namibians. Given the nature of current conditions, justification exists for a study to determine the factors associated with stock out of Nevirapine (NVP) syrup.Mixed method was employed. In which descriptive approach was employed to acquire data from a period of five years retrospectively (2012-2016) and informants from different levels of supply chain in Oshana region. Initial, order receiving is not a predictor of NVP syrup. Lack of pharmaceutical knowledge is the biggest challenge which leads to sporadic stock out of NVP syrup. Pharmaceutical knowledge of ordering NVP syrup is needed to prevent stock out of NVP syrup. It is a recommendation of this study that training is needed for staffs who are involved in ordering of pharmaceutical items.